Pemberontakan Komunis Silungkang 1926–1927 Sebuah Gerakan Islam Revolusioner - Marzali, Amri (Paradigma: Jurnal Kajian Budaya, 2020)
This article discusses what was called by the Dutch Colonial Government as ‘The Communist Uprisings of 1926-1927’. Instead of ‘the communist uprisings’, the writer tends to call this people’s resistance as ‘the Revolutionary Islamic Movement’. The writer finds the facts in which the dominant organization involved in the uprising was Sarekat Islam, a spilt faction of Sarekat Islam. The correction is based on different documents and reports, namely the resources issued by the colonial government, books written by political researchers of the West and by a local historian such as Mestika Zed, books and articles written by the local Silungkang’s experts, a book written by an actor of the movement, and the ethnographic reports written by the writer. These documents, reports, and books enable the writer to fully catch on the political, economic, social, and cultural background of ‘the Revolutionary Islamic Movement’.